2022
DOI: 10.1111/jsr.13723
|View full text |Cite
|
Sign up to set email alerts
|

Physical activity, sleep and affective wellbeing on the following day: An experience sampling study

Abstract: This study aims to investigate the temporal links between physical activity, sleep and affective wellbeing in young adults. In particular, the aim was to examine whether physical activity is associated with sleep indicators in subsequent nights and, in turn, whether sleep was associated with improved affective wellbeing the next morning.Relatedly, moderation by baseline levels of depressive symptoms, sleep quality, habitual physical activity and gender was analysed. One-hundred and forty-seven individuals (85.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…A cross-sectional study found that in adolescents, the relationship between positive and negative affect seems to be stronger associated with sleep quality than with sleep duration (Shen et al, 2018). A recent experience sampling study of university students supports these findings (Hachenberger et al, 2022). Thus, we hypothesized that greater sleep satisfaction is related to greater next day's SWB (Hypothesis 4).…”
Section: Sleep Quality/satisfactionmentioning
confidence: 72%
“…A cross-sectional study found that in adolescents, the relationship between positive and negative affect seems to be stronger associated with sleep quality than with sleep duration (Shen et al, 2018). A recent experience sampling study of university students supports these findings (Hachenberger et al, 2022). Thus, we hypothesized that greater sleep satisfaction is related to greater next day's SWB (Hypothesis 4).…”
Section: Sleep Quality/satisfactionmentioning
confidence: 72%
“…Unlike hypothesized, we did not find an effect of self-reported within-person sleep onset latency on SWB (Hypothesis 1). Previous studies described mixed results regarding the effect of sleep onset latency on sleep (see Konjarski et al, 2018 for a review)—either that short sleep onset latency was associated with better well-being at both the within- (see, e.g., Cousins et al, 2011; de Wild-Hartmann et al, 2013), and between-person level (Kouros & El-Sheikh, 2015) or that no effect was found (see, e.g., Hachenberger et al, 2023; Kalmbach et al, 2014). These findings have been reported for both self-reported and actigraphy-derived measures of sleep.…”
Section: Discussionmentioning
confidence: 99%
“…A cross-sectional study found that in adolescents, the relationship between PA and NA seems to be stronger associated with sleep quality than with sleep duration (Shen et al, 2018). A recent experience sampling study of university students supports these findings (Hachenberger et al, 2023).…”
Section: Sleep Quality/satisfactionmentioning
confidence: 92%
“…Second, there is limited evidence on how long the supposed beneficial effects of physical activity on affective wellbeing last. Some studies that investigated this aspect found evidence that acute effects of physical activity on affective states last up to approximately 3 h 16 , 19 , while another study found that the mean physical activity of a day is not associated with next day’s affect anymore 58 . While in the present study we did not examine the role of the time between the performance of physical activity and the measurement of affect, it suggests that the whole day’s average of physical activity was associated with affective states in the evening.…”
Section: Discussionmentioning
confidence: 99%